2017
DOI: 10.1589/jpts.29.2201
|View full text |Cite
|
Sign up to set email alerts
|

Effect of aquatic versus land based exercise programs on physical performance in severely burned patients: a randomized controlled trial

Abstract: [Purpose] To compare the effect of an aquatic-based versus a land-based exercise regimen on the physical performance of severely burned patients. [Subjects and Methods] Forty patients suffering from severe burn (total body surface area more than 30%) were recruited from several outpatient clinics in Greater Cairo. Their ages ranged between 20 to 40 years and were randomly assigned into two equal groups: group (A), which received an aquatic based exercise program, and group (B), which received a land-based exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…In line with the improvements in pulmonary function, the effects of water immersion on cardiac output and peripheral resistance (Wilcock et al, 2006) can lead to an increase in cardiorespiratory fitness and particularly in VO 2 max, as observed in some populations (Bocalini et al, 2008;Zoheiry et al, 2017). In this systematic review, only one study assessed cardiorespiratory fitness using the 12-min walk test and reported a small increase in the distance walked after the aquatic exercise programme (Cohen's d = 0.26).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…In line with the improvements in pulmonary function, the effects of water immersion on cardiac output and peripheral resistance (Wilcock et al, 2006) can lead to an increase in cardiorespiratory fitness and particularly in VO 2 max, as observed in some populations (Bocalini et al, 2008;Zoheiry et al, 2017). In this systematic review, only one study assessed cardiorespiratory fitness using the 12-min walk test and reported a small increase in the distance walked after the aquatic exercise programme (Cohen's d = 0.26).…”
Section: Discussionmentioning
confidence: 76%
“…In this sense, some studies have shown that water-based exercise can increase adherence comparing to other interventions because it is a comfortable environment, accessible in the community and has the extra beneficial effects of water immersion such as buoyancy (Cantarero-Villanueva et al, 2012;Dionne et al, 2018;Torres-Ronda & del Alcázar, 2014) which decreases joint stress and thus can especially benefit those with shoulder-neck mobility restrictions, pain and/or overweight (Kutzner et al, 2017;McIlroy et al, 2017;Torres-Ronda & del Alcázar, 2014). Furthermore, some studies have also found that water-based exercise can be equally effective or even superior to land-based exercise in improving muscle strength, balance, flexibility, symptom control and functional exercise capacity in different clinical populations (Bergamin et al, 2013;Bocalini et al, 2008;Siqueira et al, 2020;Zoheiry et al, 2017). Despite these initial investigations, there is still a lack of knowledge on the effects of water-…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was not been confirmed which exercise was more beneficial to improve 6MWD when AE was compared to LE in a previous meta-analysis [23]. Some studies tended to favor LE [24], while others thought that AE was better [25,26]. In our review, two studies [11,15] about the effect of AE on 6MWD in people with T2DM were analyzed.…”
Section: Discussionmentioning
confidence: 84%
“…Therefore, it was believed that VO 2max during movement in water, especially in deep water, was lower than that on land [8]. Some researchers held that VO 2max was more improved by AE than LE [25,26]. However, there is no overwhelming evidence which sport is more effective.…”
Section: Discussionmentioning
confidence: 99%